1988
DOI: 10.1051/rnd:19880813
|View full text |Cite
|
Sign up to set email alerts
|

Early effects of gossypol on the testis and epididymis in the rat

Abstract: Summary. In a previous study we showed that the administration of gossypol to rats for 34 days caused 2 types of modification of the epididymis : (1 ) the secretion of carnitine and inositol were reduced in the fluid, (2) the spermatozoa lost their motility and showed major morphological changes (head-flagella dissociation). We wished to clarify the early effects of gossypol on the epididymis. Sprague Dawley adult rats (350 g) were forced fed with gossypol at a dose of 25 mg/kg/day for 17 days. After sacrifice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…To check the antifertility effects of the released drug, the animals were sacrificed 4 days after the plasma gossypol concentration dropped to zero. The weights of testis and epididymis and the motility of spermatozoa from the cauda of the epididymis were measured . Compared to the control group, a ∼7.5, 14, and 26% decrease in testis weight, and a ∼16, 18, and 26% decrease in epididymal weight were observed for rats implanted with 10, 20, and 30-bilayer PEG/gossypol films, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…To check the antifertility effects of the released drug, the animals were sacrificed 4 days after the plasma gossypol concentration dropped to zero. The weights of testis and epididymis and the motility of spermatozoa from the cauda of the epididymis were measured . Compared to the control group, a ∼7.5, 14, and 26% decrease in testis weight, and a ∼16, 18, and 26% decrease in epididymal weight were observed for rats implanted with 10, 20, and 30-bilayer PEG/gossypol films, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…This transformation is correlated with the acquisition of motility by the spermatozoa (Jeulin et al, 1987). It has been demonstrated that, even though the epithelial cells capture and concentrate carnitine, the passage of carnitine into the spermatozoa appears to occur by passive diffusion (Jeulin et al, 1987 (Hoffer, 1983;Radigue et al, 1988). Furthermore, it is probable that this mitochondrial lesion makes the spermatozoa incapable of creating the acetyl radicals necessary for the synthesis of acetylcarnitine.…”
Section: Discussionmentioning
confidence: 99%
“…Sperm conjugating into pairs, bundles, or rouleaux is generally accepted in the literature for many mammals—except within the Rodentia order, suborder Myomorpha; specifically in the Muridae family. The first studies reporting sperm conjugation were conducted by Fornes and Burgos (, ): These authors obtained samples of epididymal content by puncturing the epididymis of the rat, Rattus norvegicus , at different regions, and placed each onto a small drop of balanced salt solution (Radigue et al, ). Samples from the caput and corpus showed individual sperm with a circular movement (caput) or circular and progressive motility (proximal corpus).…”
Section: Mammalian Sperm Conjugationmentioning
confidence: 99%